2019
DOI: 10.1088/1361-6528/ab0450
|View full text |Cite
|
Sign up to set email alerts
|

The origin of negative charging in amorphous Al2O3 films: the role of native defects

Abstract: Amorphous aluminum oxide Al 2 O 3 (a-Al 2 O 3 ) layers grown by various deposition techniques contain a significant density of negative charges. In spite of several experimental and theoretical studies, the origin of these charges still remains unclear. We report the results of extensive Density Functional Theory (DFT) calculations of native defects -O and Al vacancies and interstitials, as well as H interstitial centers -in different charge states in both crystalline α-Al 2 O 3 and in a-Al 2 O 3 . The results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 82 publications
(236 reference statements)
4
60
1
Order By: Relevance
“…It has been reported that the dominant native point defects in α-Al 2 O 3 are vacancy and interstitial defects. [14,18,30,35] Here, we revisit all dominant native defects to investigate their effect on the electrical and optical properties of α-Al 2 O 3 . i defect is a multicharged deep acceptor defect with two defect transition levels at ε(0/À1) ¼ 2.99 eV and ε(À1/À2) ¼ 4.30 eV, whereas O split i defect acts as a double donor defect with two defect transition levels at ε(þ2/þ1) ¼ 0.35 eV and ε(þ1/0) ¼ 1.44 eV.…”
Section: Native Point Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the dominant native point defects in α-Al 2 O 3 are vacancy and interstitial defects. [14,18,30,35] Here, we revisit all dominant native defects to investigate their effect on the electrical and optical properties of α-Al 2 O 3 . i defect is a multicharged deep acceptor defect with two defect transition levels at ε(0/À1) ¼ 2.99 eV and ε(À1/À2) ¼ 4.30 eV, whereas O split i defect acts as a double donor defect with two defect transition levels at ε(þ2/þ1) ¼ 0.35 eV and ε(þ1/0) ¼ 1.44 eV.…”
Section: Native Point Defectsmentioning
confidence: 99%
“…[12,13] Although several theoretical works have been carried out to study the effect of native point defects on the electronic property of Al 2 O 3 , they have not yet related them to describe the color in blue sapphire. [14][15][16][17][18][19][20][21][22] Based on the absorption spectroscopy analysis, it is concluded that there are two possible mechanisms, which is responsible for the blue coloring in sapphire: 1) the intervalence charge transfer (IVCT) of Ti-Fe pairs and 2) the transitions of intra-atomic d-d electrons in metal impurities. [12,23] Recently, Bristow et al performed the calculations using analytical force fields to study the Ti and Fe impurities in α-Al 2 O 3 and revealed that the IVCT mechanism between the Fe III -Ti III pairs is the lowest energy configuration and indeed the cause of blue coloring in sapphire.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface passivation of crystalline silicon (c-Si) solar cells can be improved using various materials such as SiO 2 [1][2][3][4][5][6], SiN x [7][8][9], Al 2 O 3 [10][11][12][13], TiO x [14][15][16], MoO x [17,18], and poly-Si [19][20][21][22]. In particular, Al 2 O 3 thin films are most widely used for boron-doped Si surfaces (or p + emitter surfaces) owing to the low surface recombination velocity (SRV) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a high density of these traps also introduces a pathway for leakage current [14]. The Al2O3 can be negatively charged by electron injection which causes the states of Ali or VO in the band gap to be occupied by electrons [15]. Hole trapping phenomenon is also observed in Al2O3 as a source of positive charging [16], [17].…”
mentioning
confidence: 99%